Knowledge, attitude and practice of HPV vaccination among female undergraduate medical students at a tertiary centre: a cross-sectional study - Kataria, Priyanka R.; Kalikar, Mrunalini V.; Dutta, Pradipta A.; Kataria, Aditya R. (International Journal Of Community Medicine And Public Health, 2025)
Background: Human papillomavirus (HPV) is a high-risk virus with less awareness and less efforts taken to combat the infection. The present study was undertaken to assess the knowledge attitude and practice about HPV and related health problems and its associated vaccine, among female medical undergraduate students to gauge their awareness levels about HPV and HPV vaccine. Methods: A cross-sectional study was carried out on 260 undergraduate (UG) female medical students from first to fourth year at an institution in Central India. A structured, pre-tested, validated questionnaire, focusing on knowledge, attitude and practice of HPV vaccine was administered to participants and the responses were gathered. The data analysis was done with Statistical Package for the Social Sciences (SPSS) Version 20 software (IBM SPSS Statistics Inc., Chicago, Illinois, USA). Results: A total of 254 students in the age range of 18 to 24 years participated in the study. The study observed inadequacies in the knowledge about certain aspects of HPV. In the present study, nearly 10% of participants were immunised for HPV. The most commonly identified reason for the lack of vaccination was ‘poor knowledge levels’ about HPV vaccine. Conclusions: The study noted an average level of knowledge about HPV and related health problems and poor knowledge levels about HPV vaccine among medical undergraduates. The study emphasises the need for educating medical students, health care professionals and the community, at large regarding HPV infection and the importance of HPV vaccination to prevent the associated sequelae.